MODELING RISK ASSESSMENT BY THE METHOD OF HIERARCHY ANALYSIS WHEN USING CLOUD IT SERVICES TECHNOLOGY - Shirinov , Laziz Toxirovich (Educational Research in Universal Sciences, 2024)
The article discusses the modeling of risk assessment using hierarchical analysis methods when using cloud IT services technology, in particular the Functional model for assessing the risks of using cloud IT services and technology technology for assessing the risks of using cloud technologies.